Leadership In Promoting Inclusive Education: Strategies And Challenges In Accommodating Student Diversity - Eka Zendriyan Pangestu; Idham; Muchammad Ibnu Muzakir; Miftah Hur Rahman Zh (At-Tathbīq: Journal of Education and Learning, 2025)
Inclusive education requires transformative leadership to secure equitable access and quality learning for all students. This qualitative case study examines the strategic role of leadership in implementing inclusive practices through in-depth interviews, focus group discussions, and participatory observations with principals, teachers, staff, and parents. The findings show that leadership is central in addressing challenges such as student diversity, limited resources, resistance to change, and weak collaboration. Leaders who apply visionary, distributed, and adaptive strategies by fostering participatory decision-making, mobilizing resources through community partnerships, and promoting flexible pedagogies successfully embed inclusive principles into school culture and daily operations. Sustaining inclusive education further demands ongoing professional development, collaborative networks with stakeholders, and systematic evaluation mechanisms. The study provides practical guidance for educational leaders and policymakers in strengthening leadership capacity and institutionalizing inclusive practices, ensuring they remain responsive, equitable, and sustainable within dynamic educational contexts.